Answer:
[tex]\frac{x^2-4}{x+2} = x-2\\\frac{4x^2-1}{2x+1} = 2x-1[/tex]
Step-by-step explanation:
a) (x2 - 4)/(x + 2)
We can simply use factorization to solve the given question.
Here the first term will be numerator and second term will be denominator.
We will factorize the numerator.
So,
[tex]\frac{x^2-4}{x+2}[/tex]
Using formula, [tex]a^2+b^2 = (a+b)(a-b)[/tex]
[tex]\frac{x^2-4}{x+2}\\= \frac{(x^2)-(2)^2}{x+2}\\=\frac{(x+2)(x-2)}{x+2}\\= x-2[/tex]
b) (4x2 - 1) / (2x + 1)
We can simply use factorization to solve the given question.
Here the first term will be numerator and second term will be denominator.
We will factorize the numerator.
[tex]\frac{4x^2-1}{2x+1}[/tex]
Using formula, [tex]a^2+b^2 = (a+b)(a-b)[/tex]
[tex]= \frac{(2x)^2-(1)^2}{2x+1}\\=\frac{(2x+1)(2x-1)}{2x+1}\\= 2x-1[/tex]
Hence,
[tex]\frac{x^2-4}{x+2} = x-2\\\frac{4x^2-1}{2x+1} = 2x-1[/tex]